DISTRIBUTION PATTERN DIFFERENCES OF KALIWANGU FORMATION IN UJUNGJAYA AND PASIR MALATI, SUMEDANG, WEST JAVA - Ilmi, Nisa Nurul; Haryanto, Iyan; Abdurrokhim, Abdurrokhim; Adhiperdhana, Billy Gumelar; Helmi, Faisal; Hutabarat, Johanes; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2019)
The distribution of Kaliwangu Formation sediment in West Java generally follows the structure of Java fold thrust belt, which directed west-east. The Java fold thurst belt was efectively formed during Pleio-Pleistocene tectonics events, in which all of the Cenozoic sediment were deformed by compression stress in north-south direction. In Ujungjaya area, Kaliwangu Formation has northwest-southeast direction, while in Pasir Malati, the formation was arced relatively in north-south direction. Kaliwangu Formation distribution in Ujungjaya was influenced by the massive compression tectonics occurred in Java. This tectonic event were occurred during Pleio-Pleistocene which resulted in Java thrust fold structure pattern including Baribis Faults. Unlike in Ujungjaya, the distribution of Kaliwangu Formation in Pasir Malati was arced in north-south direction which caused by its fold structure. There is no indication of regional fault in Pasir Malati area although a lot of fault structure was found as a part of regional structure.